Дигіталізація як сучасна тенденція розвитку інституту освіти - Шаповалов, Андрій (Видавництво Львівської політехніки, 2012)
The text considers the current situation in higher education. Particular attention is paid to this latest development trends of higher education, particularly digitization, as the trends of the 21st century. Such technological developments as the Internet and digital technologies has changed the daily practice of leisure activities and communications and now turn to educational practices. digitization of education – the process of acquisition, application and assimilation of the Institute of Education of the newest technological developments in the field of communication technology and then use them with educational, communication and educational purposes. This topic is relevant and new today.
Keywords: education; digitization; Institute of Education; globalization; trends